Motor learning - Schexnayder, B. (Techniques Magazine, 2018)
In this chapter taken from the specialist certification course curriculum, a number of concepts, terms and principles of motor learning are addressed. The terms, concepts and principles discussed in the chapter apply across all track and field event areas.